Cholesterol modulates curcumin partitioning and membrane effects - Leite, Natália B. [UNESP]; Martins, Danúbia B. [UNESP]; Fazani, Vinicius E. [UNESP]; Vieira, Maira R. [UNESP]; dos Santos Cabrera, Marcia P. [UNESP] (Elsevier, 2018)
Curcumin, a polyphenol molecule, presents a wide range of biological activities as antioxidant, anticancer, anti-inflammatory, antimicrobial and wound healing. Although some strengths attributed to curcumin derive from promiscuous biological activity, possibly because curcumin can interfere on many membrane located processes, knowledge of underlying interactions are lacking. Mammalian cell membranes characteristically contain 25 to 50% cholesterol/phospholipid ratio; however, most studies involving lipid bilayers and curcumin consider pure phosphatidylcholine and compare effects of curcumin on membranes with those of cholesterol. We investigated the interaction of curcumin with lipid bilayers containing cholesterol mimicking mammalian cells, and used spectroscopy techniques to determine partition coefficients, rigidity parameters and lytic activity. We found that curcumin partitions into different lipid bilayers (104 order coefficients that vary by less than a factor of two), containing cholesterol or not, and in the presence of sphingomyelin or phosphatidylserine. Curcumin decreases rigidity in all tested compositions, except that containing 40% cholesterol in which it increases the lipid packing order. In addition, curcumin induces leakage from giant unilamellar vesicles on a cholesterol concentration dependent way. Our results are compatible with the hypothesis of curcumin interaction with membranes being modulated by the liquid disordered phase and by the coexistence of liquid-ordered/liquid disordered phases. In bilayers containing cholesterol, curcumin assumes a more superficial location, drastically stiffens the 40% cholesterol bilayer and decreases the lytic effect. Our study may help researchers in the analysis of the biological effects of curcumin and curcumin-derived formulations by calling the attention to the discriminating role of the cholesterol content.
Keywords: Cholesterol; Curcumin; Large and giant vesicles; Lipid bilayer effects; Lipid/water partition coefficients; Phospholipid membranes